Spatial distribution of mechanical properties in Pseudomonas aeruginosa biofilms, and their potential impacts on biofilm deformation. Issue 4 (21st January 2021) - Pavissich, Juan P.; Li, Mengfei; Nerenberg, Robert
Abstract: The mechanical properties of biofilms can be used to predict biofilm deformation under external forces, for example, under fluid flow. We used magnetic tweezers to spatially map the compliance of Pseudomonas aeruginosa biofilms at the microscale, then applied modeling to assess its effects on biofilm deformation. Biofilms were grown in capillary flow cells with Reynolds numbers (Re) ranging from 0.28 to 13.9, bulk dissolved oxygen (DO) concentrations from 1 mg/L to 8 mg/L, and bulk calcium ion (Ca 2+ ) concentrations of 0 and 100 mg CaCl2 /L. Higher Re numbers resulted in more uniform biofilm morphologies. The biofilm was stiffer at the center of the flow cell than near the walls. Lower bulk DO led to more stratified biofilms. Higher Ca 2+ concentrations led to increased stiffness and more uniform mechanical properties. Using the experimental mechanical properties, fluid–structure interaction models predicted up to 64% greater deformation for heterogeneous biofilms, compared with a homogeneous biofilms with the same average properties. However, the deviation depended on the biofilm morphology and flow regime. Our results show significant spatial mechanical variability exists at the microscale, and that this variability can potentially affect biofilm deformation. The average biofilm mechanical properties, provided in many studies, should be used with caution when predicting biofilm deformation. Abstract : Magnetic tweezers were used to spatially map the elastic properties of Pseudomonas aeruginosa biofilms at the microscale, then applied modeling to assess its effects on biofilm deformation. Spatial heterogeneity was observed in all three‐dimensions, and environmental conditions had a significant impact on the spatial distribution. Modeling results indicated that the spatial heterogeneity of biofilm mechanical properties can significantly affect biofilm deformation.